Effects of adding a preceding run-up on performance, blood lactate concentration and heart rate during maximal intermittent vertical jumping - Hertogh, C.; Chamari, K.; Damiani, M.; Martin, R.; Hachana, Y.; Blonc, S.; Hue, O. (Journal of Sports Sciences, 2005)
In this study, we examined the effects of a prior run-up on intermittent maximal vertical jump performance. Seven regionally ranked male volleyball players volunteered to participate in the study. They performed three randomized tests: (1) six repeated intermittent maximal jumps (jump condition), (2) six repeated intermittent run-ups (run-up condition), and (3) six repeated run-ups followed by maximal jumps (run-up plus jump condition). All performances were assessed and blood lactate concentration and heart rate were measured before and after each of the tests. Mean (± ) jump performance (64.7±2.3cm) increased significantly (P=0.02) over the course of the jump condition and was significantly higher (P <0.001) than for the run-up plus jump condition (58.0±?3.2cm), which tended to decrease with repetition. Blood lactate concentration was significantly higher in the run-up plus jump condition (3.73±0.24mmol·l-1) than in the jump (2.61±0.26mmol·l-1, P=0.02) and run-up (2.86±0.18mmol·l-1, P=0.03) conditions. The increase in heart rate was significantly higher both in the run-up plus jump condition (33±6 beats·min-1, P=0.05) and run-up condition (33±?4 beats·min-1, P=0.02) than in the jump condition (21±3 beats·min-1). The results indicate that the addition of run-ups probably impeded performance in the repetition of vertical jumps.